248 ACUTE RENAL FAILURE DUE TO SPONTANEOUS TUMOR LYSIS SYNDROME. (1st January 2005) - Agnani, S.; Gupta, R.; Atray, N. K.; Vachharajani, T. J.
Abstract : Case 1: A 69 yr/M presented with epigastric pain, nausea and vomiting of 2 weeks duration. PE revealed signs of dehydration, epigastric tenderness and hepatomegaly. Labs: WBC: 9.9 K/mm3 (N73%, L14%, E1%, M9%), Hb 11.6 g/dL, BUN 49 mg/dL, serum creatinine (Cr) 1.7 mg/dL, AST 86 IU/L, ALT 61 IU/L, Alk. Phos. 717 IU/L and total bilirubin 3.2 mg/dL. CT abdomen: mild hepatosplenomegaly with a 1.3 cm cystic lesion in the liver. EGDscopy: prominent folds in the fundus and body of the stomach along with small duodenal erosions. Patient was treated with rabeprazole, IV fluids and discharged, but presented 5 days later with persistent symptoms and acute renal failure (ARF) with BUN 45 mg/dL, Cr 2.3 mg/dL, uric acid 18 mg/dL, phosphorus (Ph.) 6.7 mg/dL, LDH 699 U/L which progressed within 36 hours despite IV hydration to BUN 71 mg/dL, Cr 4.8 mg/dL, uric acid 24 mg/dL. Gastric biopsies showed atypical lymphocytic infiltrate suggestive of large cell lymphoma. Over the subsequent 4 days the patient recovered his renal function completely following initiation of hemodialysis. Liver and bone marrow biopsy confirmed infiltration by high-grade large cell lymphoma and chemotherapy was initiated. Case 2: A 46 yr/M with HIV on antiretroviral treatment presented with nausea, vomiting, and malaise of 2 weeks duration. PE: a cachetic male with diffuse lymphadenopathy and multiple subcutaneous nodules on the upper chest. Labs: a month before admission: BUN 15 mg/dL and Cr 1.0 mg/dL and on admission: Hb 8 g/dL, WBC 9.3 K/mm3 (N80%, L5%, M12%), K 5.6 meq/L, BUN 160 mg/dL, Cr 17.5 mg/dL, CO2 15 mmol/L, uric acid 20 mg/dL, Ph. 8.9 mg/dL. Patient was in nonoliguric ARF and was treated initially with IV hydration, allopurinol, and urinary alkalanization. Hemodialysis was initiated 24 hours later for persistent hyperuricemia. Excision biopsy of the subcutaneous chest nodule showed large B-cell lymphoma involving the dermis and subcutaneous tissue. Chemotherapy was initiated for lymphoma and the patient remained dialysis dependent until his death, possibly from CNS lymphoma, a month later. Discussion: Spontaneous tumor lysis is seen infrequently with poorly differentiated lymphomas and leukemias. These cases highlight the need to suspect spontaneous tumor lysis syndrome in patients who develop ARF in the presence of marked hyperuricemia and/or hyperphosphatemia and the need to initiate early hemodialysis in patients who are oliguric or fail to diurese.